Automation Control Targeting of a Solar Distiller - Freitas, Salomão de de; Nascimento, Ricardo Santos; Prado, Márcia Lissandra Machado (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2012: Anais do II Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2012)
This study aimed at planning, building and running an automatic solar distiller, whose function is to direct the mirror still in the position that there is a maximum brightness of the capture of the sunlight. The distiller was designed in the style of a cylindrical parabolic solar concentrator developed sheet steel, coated mirrors, modeled on a parabolic structure, with a focus along the copper tube functioning as absorber. In the parameters for the automation of the project were considered the elements of machinery, power electronics and industrial instrumentation. The results for the automation of the solar distiller, satisfied the proposed project, as it was possible to obtain the data necessary to perform the mapping and displacement of the distiller in the direction of sunlight.